Application of mapping geomorphological in potentialities and limitations discussions of the human occupation on coastal zone terrains: case study in the district - Rio Vermelho Florianópolis/Santa Catarina- Brazil - Luiz, Edna Lindaura; Lamas, Maria Maria da Rocha (Sociedade & Natureza, 2017)
This paper analyzes the characteristics of natural environments present in the district - Rio Vermelho inFlorianópolis/Santa Catarina-Brazil by realization geomorphological mapping of detail, allowing to evaluate the adequacy of human occupation on these environments. The map was elaborated in scale 1:40.000in software ArcGis using DTM (Digital Terrain Model), digital orthophoto, hillshade, interpretation ofaerial photographs and field trips. The knowledge of the characteristics of these environments shows thatsome are extremely fragile of physical point of view and shouldn’t to receive any human occupation,such as: dunes fields and the Moçambique beach, because they can quickly change their forms for bevery dynamic. While others environments may become natural hazards to the human occupation, as thecrystalline slopes and the colluvial-alluvial ramps and plains that can suffer with mass movements, runoffand torrential flows of rivers. Therefore, the results found can to serve as subsidies to different types ofterritory management in the district of Rio Vermelho, as the urban planning.